2020
DOI: 10.3892/etm.2020.9123
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae infection inhibits autophagy by alveolar type�II epithelial cells

Abstract: To investigate the molecular mechanism underlying the interaction between autophagosomes of alveolar type II epithelial (A549) cells and Klebsiella pneumoniae, an in vitro model of K. pneumoniae-infected A549 cells was established. Western blot analysis and immunofluorescence staining were used to detect the distribution of microtubule-associated protein 1A/1B-light chain 3 (LC3) and the expression of the LC3-phosphatidylethanolamine conjugate (LC3-II). K. pneumoniae-infected A549 cells were treated with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The findings are consistent with the fact that the site of contact of mitochondria with the endoplasmic reticulum induced the formation of autophagosomes . Autophagy is a self-protective cellular mechanism limiting toxicity to promote cell survival, , and autophagy could control inflammatory signaling by regulating the secretion of inflammatory mediators. , Evidence indicates that autophagy is closely related to the inflammatory response, which is consistent with our findings that DEHP-exposed quail had increased levels of TNF-α and the formation of typical autophagosomes. Therefore, this study further confirmed DEHP produced inflammation and autophagy.…”
Section: Discussionsupporting
confidence: 91%
“…The findings are consistent with the fact that the site of contact of mitochondria with the endoplasmic reticulum induced the formation of autophagosomes . Autophagy is a self-protective cellular mechanism limiting toxicity to promote cell survival, , and autophagy could control inflammatory signaling by regulating the secretion of inflammatory mediators. , Evidence indicates that autophagy is closely related to the inflammatory response, which is consistent with our findings that DEHP-exposed quail had increased levels of TNF-α and the formation of typical autophagosomes. Therefore, this study further confirmed DEHP produced inflammation and autophagy.…”
Section: Discussionsupporting
confidence: 91%
“…While our data suggest that the autophagy-inducing activity conferred to E. coli by L003 is the result of a small molecule, further work is necessary to determine the exact mechanism by which L003 induces an autophagic response in eukaryotic cells. K. pneumoniae , the predicted source of the L003 operon, has been shown to induce autophagy both in in vitro cell cultures ( Shi et al., 2020 ) as well as in an in vivo Caenorhabditis elegans model ( Kamaladevi and Balamurugan, 2017 ). This study suggests that the L003 operon should be explored for a potential role in this phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy serving as an innate immune response to defend against pathogens invading inside the host cells has been extensively studied on a set of intracellular microorganisms [ 69 ]. Despite K. pneumoniae is an extracellular pathogen, it can induce autophagy of alveolar type II epithelial (A549) cells as shown in a recent study [ 70 ], and autophagy constitutes an important mechanism to control intracellular growth of K. pneumoniae in macrophages. Enhancement of K. pneumoniae intracellular growth was observed when the autophagy process of macrophages was inhibited by bafilomycin A1, suggesting that autophagy is important for the physiological control of intracellular K. pneumoniae [ 71 ].…”
Section: K Pneumoniae Manipulates Autophagy-related Cell Sig...mentioning
confidence: 99%